2004
DOI: 10.1002/chem.200305297
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Fluorescence and Photoisomerization Studies of Azobenzene‐Functionalized Poly(alkyl aryl ether) Dendrimers

Abstract: A series of azobenzene-functionalized poly(alkyl aryl ether) dendrimers have been synthesized and their photochemical and photophysical properties in solution and as thin films have been investigated. Although the photochemical behavior of the azodendrimers in solution indicated that the azobenzene units behave independently, very similar to the constituent monomer azobenzene unit, the properties of thin solid films of the dendrimers were distinctly different. The azodendrimers, AzoG1, AzoG2, and AzoG3 were ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…) [66] has been observed, a few exceptional self-assembled bilayer aggregates of azobenzene-containing amphiphiles [67,68] and azobenzene-functionalized dendrimers [69] in aqueous solution have exhibited fluorescence emission at % 600 nm.…”
Section: à5mentioning
confidence: 97%
“…) [66] has been observed, a few exceptional self-assembled bilayer aggregates of azobenzene-containing amphiphiles [67,68] and azobenzene-functionalized dendrimers [69] in aqueous solution have exhibited fluorescence emission at % 600 nm.…”
Section: à5mentioning
confidence: 97%
“…Development of such devices requires better understanding of the photoisomerization. Some studies of azobenzenes bound to a dendrimer core have been conducted and reported in the literature (14,15). The photoisomerization mechanism, the dependence of the quantum yield on the phenyl ring substituents, the solvent properties, and the irradiation wavelength, are still not fully understood (16).…”
mentioning
confidence: 99%
“…3) indicates that the PAzoU might form the same type of aggregates in both systems. 31 The shifting of the maximum absorption to higher wavelengths (red shift) for PAzoU dissolved in solvents with different polarities as can be seen in Figure 3(inset B) shows that the DMF solvent favors the formation of J-type aggregates. 31 32 Both PAzoU LB films 4 and PAzoU cast films from DMF solutions form the same kind of aggregates.…”
Section: Pvd Film Growth-thickness Controlmentioning
confidence: 86%
“…44 However, fluorescence has been reported in thin solid films. 31 45 46 Fluorescence measurements for a PAzoU PVD film with 90 nm were carried out exciting with the 514.5 nm laser line and varying the temperature following the sequence: +20 C, 0 C, −50 C, −100 C, −150 C, 0 C, +50 C, +100 C, +150 C, +100 C, +150 C, and +20 C. Figure 8 shows the fluorescence spectra for the temperatures at 0 C, −50 C, −100 C, −150 C, +100 C, and +150 C. The PAzoU PVD fabrication process involved higher temperature than those applied in the fluorescence experiments and, accordingly to TG ( Fig. 1(b)), FTIR (Fig.…”
Section: Pvd Film Fluorescence At Different Temperaturesmentioning
confidence: 97%